PENGARUH BEBERAPA FAKTOR UTAMA TERHADAP UPAYA PENURUNAN TINGKAT KEMISKINAN DI PROPINSI NUSA TENGGARA BARAT, PERIODE 2012 – 2021 - IDA BAGUS EKA ARTIKA; IDA AYU KETUT MARINI (GANEC SWARA, 2022)
As a main priority goal in development in West Nusa Tenggara Province, the government continues to pursue poverty alleviation programs so that the number of poor people is decreasing. This study aims to determine the effect of the main factors, namely the contribution of the agricultural sector, the level of work participation, the dependency ratio and the pattern of non-food consumption on reducing poverty levels in the Province of West Nusa Tenggara. The research method is associative with data collection techniques is documentation . The results of the study found that the main factors, both the contribution of the agricultural sector and the dependency ratio had positive and significant effect in partially and simultaneously on reducing poverty levels in the Province of West Nusa Tenggara, the work participation variable and non-food consumption patterns had a negative and significant effect. The four main variables can explain the variable of reducing of poverty rate by 95.20%, and 4.80% is explained by other variables outside the model. In an effort to reduce poverty, the government of West Nusa Tenggara Province should continue to accelerate programs related to the four main variables that have been studied